(2x - 1)(4x2 + 2x + 1) = x(x-8)
<=> (2x)3 - 13 = x2 - 8x
<=> (8x3 - x2) + (8x - 1) = 0
<=> x2(8x - 1) + (8x - 1) = 0Σ
<=> (x2 + 1)(8x - 1) = 0
x2 + 1 = 0 => x2 = -1 ( vô lý )8x - 1 = 0 => 8x = 1 => x = 0,125
(2x - 1)(4x2 + 2x + 1) = x(x-8)
<=> (2x)3 - 13 = x2 - 8x
<=> (8x3 - x2) + (8x - 1) = 0
<=> x2(8x - 1) + (8x - 1) = 0Σ
<=> (x2 + 1)(8x - 1) = 0
x2 + 1 = 0 => x2 = -1 ( vô lý )8x - 1 = 0 => 8x = 1 => x = 0,125
Tìm x, biết:
a, (x+1).(x+2)-x^2-x=0
b, 2x^2+5x-3=0
Tìm GTNN của biểu thức
P= (4x^2+8x).(x^2+2x+2)-8
Tìm x :
a) 3x( x - 10 ) = x - 10
b) x( x + 7 ) - ( 4x + 28 ) = 0
c) x( x - 4 ) = 2x - 8
d) ( 2x + 3 )( x - 1 ) + ( 2x - 3 )( x - 1 ) = 0
Tìm x,biết :
a) 2x^2-7x+5=0
b) x(2x-5) - 4x+10=0
c) (x-5)(x+5) - x(x-2)=15
d) x^2(2x-3) - 12+8x=0
e) x(x - 1)+5x - 5=0
f) (2x-3)^2 - 4x(x - 1)=5
g) x(5 - 2x)+2x(x - 1)=13
h)2(x+5)(2x - 5)+(x - 1)(5 - 2x)=0
Cho biểu thức D=(x^2-2x/2x^2+8-2x^2/8-4x+2x^2-x^3)(1-1/x-2/x^2)
a. Rút gọn biểu thức D.
b.Tìm x nguyên để D nguyên
Tìm x :
a) x ( x - 1 ) - x^2 + 2x = 5
b) 4x ( 3x + 2 ) - 6x ( 2x + 5 ) + 21 ( x - 1 ) = 0
c) 2x( x + 1) - x^2 ( x + 2 ) + x^3 - x + 4 = 0
Tìm x :
a) ( 2x + 3 )^2 - 4( x - 1 )( x + 1 ) = 49
b) 16x^2 - ( 4x - 5 )^2 = 15
c) ( 2x + 1 )^2 - ( x - 1)^2 = 0
tìm x biết
a, x(2x-7)-4x+14=0
b, x(x-1)+2x-2=0
c, 2x^3+3x^2+2x+3=0
d, x^3+6x^2+11x+6=0
Rút gọn : \(\left(\frac{1+x}{x}+\frac{1}{4x^2}\right)\left(\frac{1-2x}{1+2x}-\frac{1}{1-4x^2}\times\frac{1-4x+4x^2}{1+2x}\right)-\frac{1}{2x}\)